Evaluation of an Alcohol-based Sanitizer Spray’s Bactericidal Effects on Salmonella Inoculated onto Stainless Steel and Shell Egg Processing Equipment - Musgrove , Michael T.; Northcutt, J.K. (International Journal of Poultry Science, 2012)
Improved sanitation procedures during shell egg processing may reduce the risk of food-borne illness. Experiments were conducted to determine the ability of an alcohol-quaternary ammonium sanitizer or water to reduce Salmonella inoculated onto stainless steel and shell egg processing equipment. A nalidixic acid-resistant Salmonella typhimurium (ST) isolate was grown on agar plates at 37°C for 18-24 h; cells were harvested and added to Phosphate Buffered Saline (PBS) to generate 8.5 Salmonella cells/mL inoculum in two experiments. Both experiments were repeated twice. In the first experiment four stainless steel beakers were contaminated by spraying 10 mL of inoculum, respectively. Beakers were allowed to dry for 15 min. Two of the beakers were sprayed with 20 mL of water and the other two were sprayed with a sanitizer solution (70% isopropyl alcohol and 200 ppm quaternary ammonium). After 5 min and 24 h each beaker was swabbed with a PBS moistened sponge and plated onto BGS supplemented with 200 ppm nalidixic acid to enumerate surviving ST. In the second experiment, inoculum was sprayed onto two brushes from shell egg packing machinery. After 15 min, one brush was sprayed with water for five min and the other was sprayed with the sanitizer for 30 s. Each brush was sampled by swabbing three times after 5 min and 24 h. After 5 min, 5.5 and 0.6 log CFU/mL ST and after 24 h, 2.8 and 0.0 log CFU/mL ST were recovered from stainless steel, respectively. Packer head brush average results were 4.7 and 3.1 log CFU/mL ST after 5 min and were 4.0 and 0.00 log CFU/ml ST after 24 h. This sanitizer solution and delivery system were 100 to 10,000 times more effective than water in reducing Salmonella numbers.